Motif Wartawan Televisi dalam Menerapkan Personal Branding di Instagram (LITERATUS, 2023)
The use of social media by journalists to develop their personal brands is tied to the long-term viability of the media and aids in the marketing efforts of the company. The capacity to use personal branding, which is frequently seen as an activity to exhibit and arrange in such a way that abilities and characters are shown to others, is also strongly tied to the self-value of journalists. So that the journalist stands out from the competition, personal branding can be utilized to foster emotional connections and develop relationships with the audience. This study focuses on learning the tactics and motivations used by television journalists for their personal branding activities on social media because of the significant role that personal branding is played by journalists in social media. The platform chosen for the investigation is Instagram. Researchers used descriptive qualitative study techniques to conduct informant interviews with four Instagram-active television journalists. The findings demonstrated that television journalists understand the value of using personal branding on social media to further their own interests as well as that of their profession and industry by using celebrity personalities. However, the motivation for its application is more focused on the media office's objectives and the use of personal branding while still making reference to journalistic standards.